Self-regulated learning, academic achievement and socioeconomic context at the end of primary school - Trias, Daniel; Huertas, Juan Antonio; Mels, Cindy; Castillejo, Ignacio; Ronqui, Valentina (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2021)
The increase of inequalities and the learning crisis due to COVID-19 pandemic has forced to review the role of education in the attainment of skills to learn throughout life. The purpose of this study is to investigate the incidence of the academic achievement on selfregulation strategies (forethought, inhibition and volitional inhibition), considering the socioeconomical context at the end of elementary school. The SRL strategies are assessed, from the perspective of students and teachers, triangulating measurement in different tasks. 67 students in their last year of primary education participated. The SRL measures were compared using robust tests considering high and low academic achievement and low and medium socioeconomic context (robust version of Welch’s test for two groups, Yuen’s test, and two-way ANOVA based on trimmed means and Winsorized variances). The academic achievement affects and significantly predicts the forethought strategy. In the low socioeconomical context, the students with a high academic achievement maximize their SRL. The modulating role of the school experience in self-regulation is discussed.